2017
DOI: 10.28932/jmh.v1i6.554
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Falling in Elderly Increased with Age Growth and Unaffected by Gender

Abstract: Elderly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 2 publications
1
6
0
4
Order By: Relevance
“…As human grow older, they will experience a process of degeneration and a decrease in the ability to carry out activities of daily life, so that the possessed flexibility will decrease and cause a greater risk of falling. These results are supported by the results of the analysis of (Susilo, Limyati, & Gunawan, 2017) showed that subjects at the age of 70-79 years were nine times more at risk of falling from ages 60-69 years.…”
Section: Relation Between Age Factors and The Risk Of Falls In The Elderly In The Maos Healthsupporting
confidence: 63%
See 1 more Smart Citation
“…As human grow older, they will experience a process of degeneration and a decrease in the ability to carry out activities of daily life, so that the possessed flexibility will decrease and cause a greater risk of falling. These results are supported by the results of the analysis of (Susilo, Limyati, & Gunawan, 2017) showed that subjects at the age of 70-79 years were nine times more at risk of falling from ages 60-69 years.…”
Section: Relation Between Age Factors and The Risk Of Falls In The Elderly In The Maos Healthsupporting
confidence: 63%
“…The results of this study are in line with the results of Gunawan's research (2016) that there is a relation between physical activity and the risk of falling in the elderly with a p-value = 0.010 (p <0.05). (Susilo et al, 2017). 2017) that there is a moderate and unidirectional significant relationship between daily activities and the risk of falling in research subjects (r = -0.460, p <0.01).…”
Section: The Relation Of Physical Activity Factors With the Occuranceof Falls In The Elderly Inmentioning
confidence: 97%
“…The result of research by Susilo, Limyat & Gunawan [12] explained that age influence risk falls significantly (value of p = 0.019; OR = 9), which can be interpreted that the more a person ages, the person have 9 times higher risk of fall. Age is one of the factors that cause most the older people to fall.…”
Section: Methodsmentioning
confidence: 98%
“…One of degenerative disorder that often occurs is a musculoskeletal disorder that can increase the risk of falls in older people [10]. The increase of age in older people can increase the risk of fall and is caused by several factors which consist of age, pathological conditions, environmental factors, physical, psychological, financial, cognitive and religiosity changes [11] [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation